2009
DOI: 10.1017/s1074070800002510
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty Discounting for Land-Based Carbon Sequestration

Abstract: The effect of stochastic factors on soil carbon makes the quantity of carbon generated under a sequestration project uncertain. Hence, the quantity of sequestered carbon may need to be discounted to avoid liability from shortfalls. We present a potentially applicable uncertainty discount and discuss difficulties that might arise in empirical use. We insist that the variance in historical crop yields across geographical areas is used to derive a proxy variance for forming an uncertainty discount for carbon proj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 16 publications
0
24
0
Order By: Relevance
“…In the mitigation context, Kim and McCarl (2009) [103] provides a procedure for placing a lower confidence interval on potential following a suggestion by Canada during the Kyoto Protocol discussion [104]. Such an approach could be used in an adaptation context.…”
Section: Uncertainty In Impactmentioning
confidence: 99%
“…In the mitigation context, Kim and McCarl (2009) [103] provides a procedure for placing a lower confidence interval on potential following a suggestion by Canada during the Kyoto Protocol discussion [104]. Such an approach could be used in an adaptation context.…”
Section: Uncertainty In Impactmentioning
confidence: 99%
“…Following Murray et al (2004), Kim et al (2008), and Kim and McCarl (2009), Equation 1 sets up a price discounting scheme as follows:…”
Section: Additionalitymentioning
confidence: 99%
“…They found that the theoretical mean ethanol yield varied from 1749 to 3691 L ha −1 , thus arguing that cellulosic biorefineries should consider imposing an uncertainty discount when developing their business plan. Kim and McCarl show that temporal and spatial aggregation could be used to alleviate this supply side uncertainty [19]. On the demand side, Babcock and Pouliot [20] suggested that the blend wall could be overcome by increasing incentives to use E85.…”
Section: Literature Reviewmentioning
confidence: 99%